Pengaruh Political Connection, Earnings Management, Capital Intensity, dan Inventory Intensity Terhadap Tax Avoidance pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di BEI Tahun 2019-2022 - Zarli, Jufri; Novius, Andri (Basecamp Economics PubMed, 2024)
This research is a quantitative study which aims to find out how the influence of political connections, earnings management, capital intensity and inventory intensity of tax avoidance in the manufacturing sector of various industries listed on the BEI in 2019-2022 The total sample for this research was 23 companies with the sampling method using the purposive sampling method. Data analysis uses panel data regression. The results analysis panel data regression show that partially the earnings management variable has a significant effect on tax avoidance. Meanwhile, the political connection, capital intensity and inventory intensity variables do not have a significant effect on tax avoidance. Simultaneously, political connections, earnings management, capital intensity and inventory intensity have a significant effect on tax avoidance.